NATURAL FREQUENCY OF SKEW PLATES USING FIRST-ORDER SHEAR DEFORMATION THEORY - Haryo Koco Buwono; Budiman Budiman (International Journal of Civil Engineering and Infrastructure, 2021)
This paper presents the free vibration analysis of skew plates based on the first-order shear deformation theory (FSDT). The development of finite element plates based on first-order shear deformation plate theory has been carried out and provides good results in plate element analysis. In this study, we investigate plate analysis in the case of free vibration to obtain natural frequency using one of the plate elements developed based on FSDT, numerical analysis was performed on skew plates case with varying skew angles and length to thickness ratios, the result will be used to see the convergence behavior and performance of plate element by comparing with the reference solution in the literature.